2020
DOI: 10.1055/s-0040-1714346
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Transmission of SARS-CoV-2 (COVID-19): Are Hypotheses More than Evidences?

Abstract: In spite of the increasing, accumulating knowledge on the novel pandemic coronavirus severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), questions on the coronavirus disease-2019 (COVID-19) infection transmission from mothers to fetuses or neonates during pregnancy and peripartum period remain pending and have not been addressed so far. SARS-CoV-2, a RNA single-stranded virus, has been detected in the amniotic fluid, in the cord blood and in the placentas of the infected women. In the light of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 38 publications
1
47
0
8
Order By: Relevance
“…13,14 However, as COVID-19 continued to extend throughout China and other parts of the world accompanied by increasing numbers of neonates testing positive for the virus in China and elsewhere, [15][16][17][18][19][20] the possibility of determining whether vertical transmission was occurring became of even greater importance. [21][22][23] Because vertical transmission can occur through intrauterine, intrapartum and postpartum mechanisms, the possibility that intrauterine transplacental transmission with SARS-CoV-2 was occurring in some cases was of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 However, as COVID-19 continued to extend throughout China and other parts of the world accompanied by increasing numbers of neonates testing positive for the virus in China and elsewhere, [15][16][17][18][19][20] the possibility of determining whether vertical transmission was occurring became of even greater importance. [21][22][23] Because vertical transmission can occur through intrauterine, intrapartum and postpartum mechanisms, the possibility that intrauterine transplacental transmission with SARS-CoV-2 was occurring in some cases was of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…Although COVID-19 infections among pregnant women (7,8) and newborns (9) have been reported, vertical intrauterine transmission is still a controversial issue (10,11). In certain cases, such as the one described by Kirtsman et al (12), SARS-CoV-2 RNA was detected from a nasopharyngeal swab sample collected on the day of birth before skin-to-skin contact with the mother.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the expression of ACE-2 and transmembrane protease serine type 2 receptors, which are used by the virus to enter the host cell, increases in placental and fetal tissues as the gestational age progresses [ 19 ]. Future studies are needed to investigate whether low receptor levels are protective for SARS-CoV-2 vertical transmission in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%